The Application of Tri-N in Genre-Based Indonesian Textbook for Junior High School - Siti Rochmiyati; Die Bhakti Wardoyo Putro (Universitas Sarjanawiyata Tamansiswa, 2020)
Learning Indonesian in K13 is communicative, CLIL, scientific, and genre-based. Indonesian material in junior high school is integrated in one genre. Textbooks as a learning tool compiled nationally consist of student books and teacher books. Bloom revised taxonomy, the highest ability is to create / creativity. Ki Hadjar Dewantara has long coined Tri-N (niteni, nirokke, nambahi) which is relevant to the scientific approach and the process of creating a revised edition of Bloom. Textbooks as a principal guide for teachers and students in learning must apply a scientific approach. Tamansiswa teachings are known as Tri-N. Niteni is the process of marking by paying close attention, using all the senses, digging deeper information, and reasoning by connecting knowledge already possessed from excavated products. Nirokke is imitating what is taught through a model / example / example from the teacher / learning resource by involving the mind, sensing, feeling / conscience and spirituality integrally and harmoniously. Nambahi is the process of adding to what he has learned in developing his creativity and ideas through the activities of designing, creating, and improvising. This study aims to describe the application of the niteni, nirokke, and supplementary processes in genre-based Indonesian SMP textbooks. The research method used is descriptive qualitative analysis of interactive models Miles Huberman. The genres representing this research are description, explanation, procedure, exposition, and narrative genres. The results showed that in these genres the process of niteni, nirokke, and nambahi always appeared.